1975
DOI: 10.1063/1.431835
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of vibrational relaxation in the HF–DF, HF–CO2, and DF–CO2 systems. II

Abstract: Measurements of vibrational energy transfer probabilities are presented for the temperature range 205-360'K for HF-DF, HF-CO" and DF-CO, gas mixtures. The present results provide an accurate determination of the inverse temperature dependence of the energy transfer probabilities exhibited by these systems. Large deactivation effects caused by HF (DF) polymers were observed for temperatures below 220'K.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

1978
1978
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…We begin by using the compilation of collisional transfer rates assembled by Dzelzkalns and Kaufman, 54 from which they determined the probability for the process in question to be 0.0036, based upon a Lennard-Jones total collision rate. As shown by the experimental results summarized by Lucht and Cool,53 this rate increases with decreasing temperature, namely as T (Ϫ1. 34) .…”
Section: Comparison With Full Collision Experimentsmentioning
confidence: 72%
See 1 more Smart Citation
“…We begin by using the compilation of collisional transfer rates assembled by Dzelzkalns and Kaufman, 54 from which they determined the probability for the process in question to be 0.0036, based upon a Lennard-Jones total collision rate. As shown by the experimental results summarized by Lucht and Cool,53 this rate increases with decreasing temperature, namely as T (Ϫ1. 34) .…”
Section: Comparison With Full Collision Experimentsmentioning
confidence: 72%
“…Vibrational energy transfer between HF and CO 2 in full collisions has been studied in great detail [46][47][48][49][50][51][52][53][54] and it is instructive to compare these with the results of the present study. We begin by noting that numerous studies have shown that HF (vϭ1) relaxes collisionally with CO 2 via the V -V process discussed above, namely by coupling to the CO 2 (00 0 1) asymmetric stretching vibrational state.…”
Section: Comparison With Full Collision Experimentsmentioning
confidence: 99%
“…The result is shown in Fig. 2, together with the available experimental 2329 and previous theoretical 31,32 data. Our quantum mechanical rate coefficient initially decreases with temperature from 100 to 500 K, but increases slowly with temperature from 500 to 1200 K, with a minimum value of 2.1 × 10 −12 cm 3 s −1 mole −1 at 500 K. The calculated rate coefficient (3.03 × 10 −12 cm 3 s −1 mole −1 ) is in quite good agreement with the experimental result of 3.0 × 10 −12 cm 3 s −1 mole −1 at 200 K, reported by Hancock and Green 23 .…”
Section: Resultsmentioning
confidence: 63%
“…2Calculated vibrational-resolved (1; 0) → (0; 0) rate coefficient as a function of temperature. The current calculated results are compared with available experimental (denoted as Expt 1 23 , Expt 2 24 , Expt 3 25 , Expt 4 26 , Expt 5 27 , Expt 6 28 , Expt 7 29 , and Expt fitting 22 ) and other theoretical results (Theo 1 31 and Theo 2 32 ). All error bars represent the experimental error…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation